2018
DOI: 10.1007/s00415-018-8778-y
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole and other prognostic factors in ALS: a population-based registry study in Italy

Abstract: Independently from other prognostic factors, patients who received riluzole for a longer period of time survived longer, but further population based studies are needed to verify if long-tem use of riluzole prolongs survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…Of note is also that in our population the C9orf72 expansion was associated with lower odds of spinal onset, NIV, hypertension, and psychiatric diseases. This evidence was not unexpected with regard to the lower odds of association between the C9orf72 expansion and spinal onset and NIV, in consideration of the above discussed higher odds of association between the C9orf72 expansion and bulbar onset, among possible onsets, and given the higher association between the C9orf72 expansion and dementia, proven to induce less adherence and compliance to treatments, including NIV (Govaarts et al, 2016; Mandrioli et al, 2018b).…”
Section: Discussionmentioning
confidence: 81%
“…Of note is also that in our population the C9orf72 expansion was associated with lower odds of spinal onset, NIV, hypertension, and psychiatric diseases. This evidence was not unexpected with regard to the lower odds of association between the C9orf72 expansion and spinal onset and NIV, in consideration of the above discussed higher odds of association between the C9orf72 expansion and bulbar onset, among possible onsets, and given the higher association between the C9orf72 expansion and dementia, proven to induce less adherence and compliance to treatments, including NIV (Govaarts et al, 2016; Mandrioli et al, 2018b).…”
Section: Discussionmentioning
confidence: 81%
“…Current and past use of riluzole was associated with longer time to hospice referral. This could be due to participants choosing more aggressive treatments aimed at prolonging survival, which delay their entry into hospice, which has been seen in other registry studies (39,40). All study participants were alive so we were unable to estimate any differences in survival.…”
Section: Discussionmentioning
confidence: 98%
“…14 Recent registry-based cohort studies (all class III) have estimated an improvement in median survival with riluzole treatment of 7.3 months, 15 10 months 16 or 12 months, 17 but other studies have found no effect on survival. [18][19][20][21] Findings • Palliative care should be introduced if there is severe physical (i.e., pain, dysphagia or dyspnea), psychosocial or existential distress (EC).…”
Section: Disease-modifying Therapiesmentioning
confidence: 99%